Corporate Rebranding and Crisis Communication in the Era of Cancel Culture: A Case Study of Cracker Barrel’s 2025 Logo Controversy - Ligina Tri Surya Raudhah (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study examines the dynamics of corporate rebranding and crisis communication in the era of cancel culture through the case of the Cracker Barrel 2025 logo controversy. The research aims to analyze how rebranding decisions may trigger reputational crises and how crisis communication strategies influence public trust recovery. A qualitative case study approach was employed using documentary analysis of secondary data collected between March and May 2025. The dataset consisted of 35 documents, including official company statements, news articles from major media outlets, corporate press releases, and public responses posted on digital platforms and social media. Data were analyzed using thematic analysis guided by Situational Crisis Communication Theory (SCCT) and Corporate Rebranding Theory. The findings reveal that the removal of Cracker Barrel’s iconic “Old Timer” figure generated strong negative reactions because consumers perceived the change as a loss of brand authenticity. The crisis rapidly intensified through digital platforms, where cancel culture amplified criticism and transformed visual changes into broader cultural debates. Based on SCCT, the crisis was categorized as preventable, resulting in high public attribution of responsibility toward the company. Although Cracker Barrel attempted recovery through a rebuild strategy by withdrawing the new logo and issuing a public statement, short-term public trust recovery remained limited. This study concludes that rebranding in the digital era requires balancing modernization with identity preservation, while crisis communication should address both rational and emotional dimensions of consumer perception. Effective brand transformation therefore depends on transparent, strategic, and consumer-oriented communication practices.